Climate Change and Chronic Food Insecurity in Sub-Saharan Africa - Salgado Baptista, Diogo Miguel (Departmental Papers; Departmental Paper ;, 2022)
Climate change is intensifying food insecurity across sub-Saharan Africa (SSA) with lasting adverse macroeconomic effects, especially on economic growth and poverty. Successive shocks from the war in Ukraine and COVID-19 pandemic have increased food prices and depressed incomes, raising the number of people suffering from high malnutrition and unable to meet basic food consumption needs by at least 30 percent to 123 million in 2022 or 12 percent of SSA's population. Addressing the lack of resilience to climate change-that critically underlies food insecurity in SSA-will require careful policy prioritization against a backdrop of financing and capacity constraints. This paper presents some key considerations and examples of tradeoffs and complementarities across policies to address food insecurity. Key findings include (1) Fiscal policies focused on social assistance and efficient public infrastructure investment can improve poorer households' access to affordable food, facilitate expansion of climate-resilient and green agricultural production, and support quicker recovery from adverse climate events; (2) Improving access to finance is key to stepping up private investment in agricultural resilience and productivity as well as improving the earning capacity and food purchasing power of poorer rural and urban households; and (3) Greater regional trade integration, complemented with resilient transport infrastructure, enables sales of one country's bumper harvests to its neighbors' facing shortages. The international community can help with financial assistance-especially for the above-mentioned social assistance and key infrastructure areas-capacity development, and facilitating transfers of technology and know-how.